Efficient Synthesis of Pyrido[3,4-c]cinnolines and Pyrido[3,2-c]cinnolines by Intramolecular Azo Coupling Reaction of 4,6-Diaryl-3-pyridine Diazonium Salts and Study of Their Antiviral Activity - Fisenko, Alina Yu.; Shuvalov, Vladislav Yu.; Arshinov, Evgenii V.; Glizdinskaya, Larisa V.; Shishkina, Larisa N.; Bormotov, Nikolay I.; Serova, Olga A.; Sagitullina, Galina P. (Synthesis, 2024)
A new method is proposed for the synthesis of pyrido[3,4-c]cinnolines and pyrido[3,2-c]cinnolines. Pyridine-3-diazonium tetrafluoroborates, containing donor methoxy groups in one of the aryl substituents, form pyridocinnolines at 0 °C by intramolecular azo coupling reaction. The 2′-methoxy group in the aryl substituent of the pyridine-3-diazonium salt participates in the aromatic nucleophilic substitution reaction, which results in the elimination of the diazo group to form benzofuro[2,3-c]pyridine and benzofuro[3,2-b]pyridine. The intermediate and target reaction products were isolated in high yields.
Keywords: azo coupling reaction; 3-aminopyridine; benzofuro[2,3-c]pyridine; benzofuro[3,2-b]pyridine; pyrido[3,4-c]cinnoline; pyrido[3,2-c]cinnoline